PERLINDUNGAN HUKUM TERHADAP KREDITOR ATAS OBJEK JAMINAN HAK TANGGUNGAN YANG DIRAMPAS NEGARA - Najlaa Putri Virdiansyah (2023)
The debt events are generally aimed at in the form of a basic agreement followed by a guarantee agreement for both the debt and the individual one of the agencies of guarantee is the Right of Representation whose existence is regulated in UUHT. The guarantee's role is to offer legal certainty on debt repayment, so that if the debtor fails to promise at any time, such guarantee may be performed in order to return the debtor's debt. However, it becomes a problem when the debtor becomes liable in the case of corruption criminal offences and is aware of the liability rights guaranteed to the creditor are derived or obtained from the criminal offence and, according to the applicable rules, the object will be deprived of the state. As a result of such a robbery, the creditor is likely to suffer losses and will be unable to receive repayment. According to the findings of this study, the type of legal protection obtained by creditors whose rights are deprived of liability by the state can be preventive and repressive legal protection, and creditors can still enforce the security of the liability even if the security has changed hands. According to the research, there is an urgent need to approve the Asset Depreciation Act in order to maximize the protection of third parties who have been wounded, as well as the insertion of a language on extra guarantees to ensure legal certainty of debt payback to creditors.